The abnormal umbilical venous–arterial index in the second half of pregnancy is associated with fetal outcome: A retrospective cross-sectional study - Wang, Ling; Zhou, Dan; Long, Baiguo; Wang, Jiqing; Li, Lingling; Peng, Yang; Zhou, Qichang; Zeng, Shi (Frontiers in Pediatrics, 2023)
Objective: This study aims to observe the changes of the umbilical venous–arterial index (VAI) and investigate its predictive power for fetal outcome during the second half of pregnancy. Methods: Fetuses with gestational age (GA) at 24 to 40 weeks were collected. According to the outcome score, neonates with outcome scores of 0, 1, or 2 were assigned to the control group, whereas those with scores of 3–12 were assigned to the compromised group. VAI was calculated as the ratio of normalized umbilical vein blood flow volume and umbilical artery pulsatility index. Regression analysis was performed to obtain the best-fitting curves between VAI and GA in the controls. Doppler parameters and perinatal outcomes were compared in both groups. Receiver operating characteristic analysis was used to assess the diagnostic performance of the VAI. Results: A total of 833 (95%) fetuses had Doppler parameters and pregnancy outcomes documented. Compared with the controls, the VAI was significantly lower in the compromised group (83.2 vs. 184.8ml/min/kg, p<0.001). The sensitivity and specificity of VAI to predict compromised neonates were 95.15% (95% Cl, 89.14 to 97.91%) and 99.04% (95% CI: 98.03 to 99.53%), respectively at a cutoff value of 120 ml/min/kg. Conclusions: VAI presents better diagnostic performance than umbilical vein blood flow volume and umbilical artery pulsatility index. A cutoff value of 120 ml/min/kg might be used as the warning value for predicting the fetal outcome.